Sialylated N‐glycans mediate monocyte uptake of extracellular vesicles secreted from Plasmodium falciparum‐infected red blood cells. Issue 2 (21st March 2022) - Ben Ami Pilo, Hila; Khan Khilji, Sana; Lühle, Jost; Biskup, Karina; Levy Gal, Bar; Rosenhek Goldian, Irit; Alfandari, Daniel; Revach, Or‐Yam; Kiper, Edo; Morandi, Mattia I.; Rotkopf, Ron; Porat, Ziv; et al.
Abstract: Glycoconjugates on extracellular vesicles (EVs) play a vital role in internalization and mediate interaction as well as regulation of the host immune system by viruses, bacteria, and parasites. During their intraerythrocytic life‐cycle stages, malaria parasites, Plasmodium falciparum ( Pf ) mediate the secretion of EVs by infected red blood cells (RBCs) that carry a diverse range of parasitic and host‐derived molecules. These molecules facilitate parasite‐parasite and parasite‐host interactions to ensure parasite survival. To date, the number of identified Pf genes associated with glycan synthesis and the repertoire of expressed glycoconjugates is relatively low. Moreover, the role of Pf glycans in pathogenesis is mostly unclear and poorly understood. As a result, the expression of glycoconjugates on Pf ‐derived EVs or their involvement in the parasite life‐cycle has yet to be reported. Herein, we show that EVs secreted by Pf ‐infected RBCs carry significantly higher sialylated complex N ‐glycans than EVs derived from healthy RBCs. Furthermore, we reveal that EV uptake by host monocytes depends on N‐glycoproteins and demonstrate that terminal sialic acid on the N ‐glycans is essential for uptake by human monocytes. Our results provide the first evidence that Pf exploits host sialylated N ‐glycans to mediate EV uptake by the human immune system cells.